Pengembangan Naskah Drama Materi Menjadi Berkat Bagi Sesama Dalam Menumbuhkan Sikap Berbagi - Sartika S Tamba (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The purpose of this study was to develop drama scripts in Menjadi Berkat Bagi Sesama in developing attitudes in fostering sharing in grade 5 students through Christian religion education. Sample is 61 teachers PAK IN Kec. Tarutung and Kec. Sipoholon, where 31 teachers as research and 30 teachers for instrument test. This research using development research with procedure model ADDIE which was developed Dick Carry, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the research it was concluded that the drama script is very necessary as a learning medium by PAK teachers when teaching material  Menjadi Berkat Bagi Sesama in fostering shared attitudes for students.